Wives and Wanderers in a New Guinea Highlands Society Women's lives in the Wahgi Valley - Reay, Marie Olive (ANU Press, 2022)
Wives and Wanderers in a New Guinea Highlands Society brings to the reader anthropologist Marie Reay's field research from the 1950s and 1960s on women's lives in the Wahgi Valley, Central Highlands of Papua New Guinea. Dramatically written, each chapter adds to the main story that Reay wanted to tell, contrasting young girls' freedom to court and choose partners, with the constraints (and violence) they were to experience as married women. This volume provides readable ethnographic material for undergraduate courses, in whole or in part. It will be of interest to students and scholars of gender relations, anthropology and feminism, Melanesia and the Pacific. The material in this book, which Reay had written by 1965 but never published, remains startlingly contemporary and relevant. Marie Olive Reay was a social anthropologist who did research in Australian Indigenous communities and in the Wahgi Valley in the Central Highlands of Papua New Guinea. Employed at The Australian National University from 1959 to 1988 when she retired, Reay passed away in 2004. In 2011 this manuscript was found in her personal papers, reconstructed and edited by Francesca Merlan, augmented here by an additional introduction by eminent anthropologist of the Highlands, and of gender, Marilyn Strathern. Had this manuscript appeared when Reay apparently completed it in its present form - around 1965 - it would have been the first published ethnography of women's lives in the Central Highlands of Papua New Guinea. Its retrieval from Reay's papers, and availability now, adds a new dimension to works on gender relations in Melanesian societies, and to the history of Australian and Pacific anthropology. ; Wives and Wanderers in a New Guinea Highlands Society brings to the reader anthropologist Marie Reay's field research from the 1950s and 1960s on women's lives in the Wahgi Valley, Central Highlands of Papua New Guinea. Dramatically written, each chapter adds to the main story that Reay wanted to tell, contrasting young girls' freedom